Couple dynamics and interaction needs with healthcare professionals in long-term neurological rehabilitation: A hermeneutic qualitative study - Alexa von Bosse; Peter König; Eva Jansen (SSM: Qualitative Research in Health)
Background: Acquired neurological diseases significantly alter the dynamics between patients and their caregiving relatives, particularly spouses. This study investigates how these disorders impact the patient-spouse relationship and assesses the role of healthcare professionals in shaping these dynamics during long-term rehabilitation. Methods: We conducted three comprehensive, in-depth sequential analyses that focused on (1) patients, (2) spouses, and (3) both partners within their relationship. Using a dynamic interactionist approach, narrative interviews with couples provided insights from both partners on relationship dynamics. Data analysis followed the documentary method, emphasizing socio-genetic type building to classify patient, caregiver, and relationship types. Results: We identified four patient types, four caregiver types, and three relationship types, each with distinct social interaction patterns and specific rehabilitation needs. Our model, based on symbolic interactionism and Baxter's Relational Dialectics Theory, underscores the fluid and evolving nature of these roles. Patients and caregivers can transition between different types due to the chronic nature of the disorder and the social context of rehabilitation. Recognizing these shifts is essential for addressing relational and social aspects in therapy. Conclusion: The findings highlight the necessity of acknowledging the dynamic and varied needs of patients and caregivers as well as the relationship dynamics. By understanding relationship types and interactions, healthcare professionals can develop personalized therapeutic strategies that enhance patient- and family-centred care, vital for improving rehabilitation outcomes.